2014
DOI: 10.1136/bcr-2014-206760
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cell histiocytosis presenting as hypothyroid goitre: a unique presentation

Abstract: Langerhans cell histiocytosis (LCH) is a disease involving the antigen presenting cells, which can range from a single system involvement with an indolent course to a multisystem disease with increased morbidity. We present a rare case of LCH presenting as hypothyroid goitre that was successfully treated as per the LCH III trial protocol with a combination of vinblastine and oral prednisolone. We highlight the need for awareness of this rare presentation of LCH as a painless goitre which is often misdiagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…7 Studies have suggested that, serum alkaline phosphatase levels and thyroids hormones should be checked to explore other factors contributing to the early loss of teeth. 1,10,14 In this case, periodontitis was the sole manifestation, and the patient reported neither pain nor facial swelling. The differential diagnosis considered prepubertal periodontitis due to periodontal involvement, but this was ruled out due to the absence of bacterial or hormonal factors.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…7 Studies have suggested that, serum alkaline phosphatase levels and thyroids hormones should be checked to explore other factors contributing to the early loss of teeth. 1,10,14 In this case, periodontitis was the sole manifestation, and the patient reported neither pain nor facial swelling. The differential diagnosis considered prepubertal periodontitis due to periodontal involvement, but this was ruled out due to the absence of bacterial or hormonal factors.…”
Section: Discussionmentioning
confidence: 72%
“…In unifocal bone involvements, a slight curettage during biopsy may accelerate healing, and no additional intervention may be necessary 7 . Studies have suggested that, serum alkaline phosphatase levels and thyroids hormones should be checked to explore other factors contributing to the early loss of teeth 1,10,14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it can be confused with other far more common thyroid diseases and the misdiagnosis rate is not low. 7 Considering the LCH is a multisystemic disease and has a high misdiagnosis rate, the diagnosis of LCH involving the thyroid or multisystem can be a medical puzzle. Although the diagnostic thyroidectomy was considered as an exact diagnostic method for LCH involving thyroid, it had a lot of complications after thyroidectomy and had no benefit for multisystem LCH.…”
Section: Discussionmentioning
confidence: 99%